Resistensi dalam E-Cerpen Karya Muna Masyari dan Relevansinya terhadap Pembelajaran Bahasa dan Sastra Indonesia - Dinda Triana Cindi; Karkono Karkono; Azizatuz Zahro (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
One type of literary work that is accepted and quite popular in society is the short story. The increasingly rapid development of technology means that short stories, which were originally only in print or book form, are now available electronically or digitally (E-Short Stories). In short stories, sometimes there is criticism that the author wants to convey against the background of existing problems. Muna Masyari, as one of the Madurese authors, presents criticism in the short stories she writes as a form of resistance to the problems that occur in the Madurese community's life system, especially in the cultural system. The aim of this research is to describe open and closed resistance in Muna Masyari's E-Story and its relevance to learning Indonesian language and literature. The method used in this research is a qualitative descriptive method. Data in the form of words, sentences and paragraphs containing open and closed forms of resistance in Muna Masyari's e-short stories and their relevance to learning Indonesian language and literature. Meanwhile, the data source for this research is E-Story by Muna Masyari. The data collection technique in this research uses document study. Then, the data analysis technique uses Miles & Huberman's interactive analysis technique. The research results show that there are 2 forms of resistance, namely open and closed resistance in Muna Masyari's e-short stories, as well as works created by authors that are relevant if used as learning content for Indonesian language and literature.